THE EFFECT OF DIGITAL BANKING IMPLEMENTATION ON CUSTOMER SATISFACTION (CASE STUDY OF BSI DIGITAL BANKING USER CUSTOMERS) - Sri Wahyuni; Nurbaiti Nurbaiti; Nur Ahmadi Bi Rahmani (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This study aims to determine the extent to which the influence of Accuracy (X1), Speed (X2), Security (X3) affects customer satisfaction at Bank BSI KCP S. Parman. This study uses a quantitative approach with sampling using the Non Probability Sampling method. The type of data used in this study is primary data obtained from questionnaires filled out by respondents directly. And secondary data that comes from books, journals, research results, practical work reports and related to the author's research objects. In this study, the population that will be taken is all BSI KCP S. Parman customers in 2022 as many as 9,950 people. The analysis tool uses multiple linear regression analysis. The results of the study show that the variables Accuracy (X1), Speed (X2), Security (X3) simultaneously affect customer satisfaction using digital banking BSI KCP S. Parman. The coefficient of determination value is 0.741. This means that 74.1% of bank existence is influenced by Accuracy (X1), Speed (X2), and Security (X3), while the remaining 25.9% of customer satisfaction is influenced by other variables not examined in this study.